2017
DOI: 10.1539/joh.16-0119-oa
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between non-standard work arrangements and work-related accident absence in Belgium

Abstract: Objectives:The main objective of this study is to examine the relationship between indicators of nonstandard work arrangements, including precarious contract, long working hours, multiple jobs, shift work, and work-related accident absence, using a representative Belgian sample and considering several sociodemographic and work characteristics. Methods : This study was based on the data of the fifth European Working Conditions Survey ( EWCS ) . For the analysis, the sample was restricted to 3343 respondents fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…Because of the large variation in exposure and outcome definitions as well as measurement methods, a meta-analysis was not feasible. However, when grouping similar exposures together, the risk for occupational injuries was consistently higher for those performing multiple jobs compared with one (15,16,20,21) and among those employed through a subcontractor at the same worksite or staffing agency (14,22,23). The latter has also been found in a research report by the Swedish Work Environment Agency, which did not the meet the peer-reviewed criteria for inclusion (30).…”
Section: Highmentioning
confidence: 85%
See 2 more Smart Citations
“…Because of the large variation in exposure and outcome definitions as well as measurement methods, a meta-analysis was not feasible. However, when grouping similar exposures together, the risk for occupational injuries was consistently higher for those performing multiple jobs compared with one (15,16,20,21) and among those employed through a subcontractor at the same worksite or staffing agency (14,22,23). The latter has also been found in a research report by the Swedish Work Environment Agency, which did not the meet the peer-reviewed criteria for inclusion (30).…”
Section: Highmentioning
confidence: 85%
“…Five studies investigated the relation between temporary contracts and risk of injuries. One of these found a statistically significant positive association (14), while four studies showed inconclusive results or negative associations (20,(24)(25)(26). Four studies on part-time or casual work suggested negative or no relation to occupational injuries (18,19,25).…”
Section: Dimensions Of Precarious Employment Studied and Their Associmentioning
confidence: 97%
See 1 more Smart Citation
“…Work in multiple jobs and working for temporary agencies were the two areas of non-standard work arrangements providing the strongest evidence of elevated risk of work-related injury. All four studies on multiple job holding (11)(12)(13)(14) reported increased risk of work-related injury when working in multiple jobs as compared with single jobs (with 3 of the 4 being statistically significant). Dong et al's longitudinal study (12) demonstrated a strong dose-response relationship where every additional job resulted in increased risk to a cohort of construction workers.…”
Section: Editorialmentioning
confidence: 99%
“…Therefore, to analyze work accidents, it is necessary to consider both, the individual factors and those concerning the work activity (Alali et al, 2017). This is because it is already a consensus that an environment with poor working conditions, physical and mental load and stress increases the chances of accidents.…”
Section: Physical and Psychosocial Stress And Healthrelated Factorsmentioning
confidence: 99%